The Mechanical Behavior of Salt X PROCEEDINGS OF THE 10TH CONFERENCE ON THE MECHANICAL BEHAVIOR OF SALT (SALTMECH X), UTRECHT, THE NETHERLANDS, 06-08 JULY 2022 - de Bresser, J.H.P; Drury, M.R; Fokker, P. A.; Gazzani, M.; Hangx, S.J.T; Niemeijer, A.R; Spiers, C.J (Taylor & Francis, 2022)
Rock salt formations have long been recognized as a valuable resource - not only for salt mining but for construction of oil and gas storage caverns and for isolation of radioactive and other hazardous wastes. Current interest is fast expanding towards construction and re-use of solution-mined caverns for storage of renewable energy in the form of hydrogen, compressed air and other gases. Evaluating the long term performance and safety of such systems demands an understanding of the coupled mechanical behavior and transport properties of salt. This volume presents a collection of 60 research papers defining the state-of-the-art in the field. Topics range from fundamental work on deformation mechanisms and damage of rock salt to compaction of engineered salt backfill. The latest constitutive models are applied in computational studies addressing the evolution and integrity of storage caverns, repositories, salt mines and entire salt formations, while field studies document ground truth at multiple scales. The volume is structured into seven themes: Microphysical processes and creep models Laboratory testing Geological isolation systems and geotechnical barriers Analytical and numerical modelling Monitoring and site-specific studies Cavern and borehole abandonment and integrity Energy storage in salt caverns The Mechanical Behavior of Salt X will appeal to graduate students, academics, engineers and professionals working in the fields of salt mechanics, salt mining and geological storage of energy and wastes, but also to researchers in rock physics in general.